Among My Books. Second Series - Lowell, James Russell, 1819-1891 (Salt Lake City, UT : Project Gutenberg, 2005)
"Among My Books. Second Series" by James Russell Lowell is a collection of literary essays written during the mid-19th century. This work offers insights into the works of various influential writers, reflecting on their contributions to literature and culture, with specific focus in the opening part on the life and impact of the poet Dante Alighieri. Lowell explores not only Dante's literary genius but also the historical and cultural context of his life, revealing the profound influence of his experiences on his writing. The beginning of this work introduces readers to Lowell's admiration for Dante, establishing the poet's significance in literature. It details Dante's origins in Florence, his education, and the tumultuous political landscape that shaped his life. As Lowell vividly describes Dante's contributions to art and poetry, he highlights key events, such as Dante's exile from Florence, which sparked his most famous works. The exploration of Dante$1 (Bs complex character, shaped by love, loss, and his artistic ambition, sets the tone for a deeper examination of his enduring legacy in the following essays. (This is an automatically generated summary.)s
Dante -- Spenser -- Wordsworth -- Milton -- Keats.
Release date is 2005-07-01
E-text prepared by Ted Garvin, Thomas Berger, and the Online Distributed Proofreading Team
Keywords: Keats, John, 1795-1821; Milton, John, 1608-1674; Dante Alighieri, 1265-1321; Wordsworth, William, 1770-1850; Spenser, Edmund, 1552?-1599